The Politics of Conflict Resolution: Negotiating Public Policy Amidst Community Dissonance - Zulfan Nahruddin (Journal of Public Representative and Society Provision, 2022)
The politics of conflict resolution are investigated in this study as they pertain to the process of negotiating public policy in the face of community dissonance. The study examines the strategies and approaches that are used to mediate conflicts and disputes that may emerge during the process of developing and implementing policy using qualitative approach as its research methodology. According to the findings of the research, the most important aspects of successfully negotiating public policy in communities where there is discord are participation, inclusive decision-making, confronting power inequalities, effective communication, and sufficient resources. The conclusions of the research have significant repercussions for the process of formulating and enacting policy, and they emphasize the necessity of taking into account the various points of view and interests of the stakeholders concerned. The research makes a contribution to the existing body of literature on the topic of negotiating public policy in the face of community disagreement and offers insights into the strategies and approaches that are necessary to achieve successful policy outcomes.